Hypermethylated GRIA4, a potential biomarker for an early non-invasive detection of metastasis of clinically known colorectal cancer - Lukacova, Eva; Burjanivova, Tatiana; Podlesniy, Petar; Grendar, Marian; Turyova, Eva; Kasubova, Ivana; Laca, Ludovit; Mikolajcik, Peter; Kudelova, Eva; Vanochova, Andrea; Miklusica, Juraj; Mersakova, Sandra; et al. (Frontiers in Oncology, 2023)
Introduction Colorectal cancer (CRC) can develop through several dysregulated molecular pathways, including the serrated pathway, characterized by CpG island methylator (CIMP) phenotype. Although the tumor tissue is a commonly tested material, sample types such as stool or plasma, bring a new, non-invasive approach. Several cancer-related methylated genes have been identified in CRC patients, including gene GRIA4, showing promising diagnostic potential. The aim of our study was to develop a sensitive droplet digital PCR (ddPCR) assay to examine GRIA4 hypermethylation status in CRC patients and evaluate its diagnostic potential in tissue and liquid biopsy samples. Methods In total, 23 patients participated in this study, 7 patients with primary CRC and 16 patients with liver metastasis of clinically known CRC. We obtained tumor and non-tumor tissues (N=17), blood samples pre- and post-surgery (N=22), and blood of five volunteers without a personal cancer history. We have developed and optimized a ddPCR assay for GRIA4 hypermethylation detection, from tissue and plasma samples. Results We detected significantly increased GRIA4 methylation in tumor tissues compared to their adjacent non-tumor tissue, p<0.0001. Receiver operating characteristic (ROC) analysis defined cutoff values to separate primary tumors and metastases from non-tumor colon/rectum, specifically 36.85% for primary tumors and 34.81% for metastases. All primary tumors were above this threshold. When comparing the methylation levels of metastatic vs. non-tumor tissue, a smaller increase was observed in liver metastasis versus colon tissue (3.6× gain; p=0.001), then in liver metastasis versus adjacent liver tissue (17.4× gain; p<0.0001). On average, GRIA4 hypermethylation in primary tumor plasma was 2.8-fold higher (p=0.39), and in metastatic plasma, 16.4-fold higher (p=0.0011) compared to healthy individuals. Hypermethylation in metastatic plasma was on average 5.9 times higher (p=0.051) than in primary tumor plasma. After tumor removal surgery, average hypermethylation decrease in plasma was 1.6× for primary (p=0.037) and 4.5× for metastatic patients (p=0.023). Discussion Based on our data, it can be inferred that GRIA4 serves as a tissue specific biomarker for the colon/rectum tissue, thus is suitable for cancer classification. This biomarker showed the potential to be an attractive target for early non-invasive detection of metastases of clinically known CRC, although additional analysis has to be performed.